Pengembangan Media Pembelajaran Video Animasi Berbasis PBL (Problem Based Learning) dalam Pembelajaran IPAS Kelas IV SD - Fajriah, Fadillah Nuroini; Erita, Yeni; Desyandri, Desyandri; Arwin, Arwin (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the low learning motivation of students caused by the limited variety of learning media used in the classroom. The purpose of this study was to develop and produce learning media in the form of animation videos based on Problem Based Learning (PBL) in IPAS subjects that are valid, practical, and effective for fourth-grade elementary school students. The study used the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. Validation was carried out by experts in media, material, and language with results of 87.67%, 92.72%, and 96.66%, respectively, all of which were classified as highly valid. The practicality test at SDN 006 Mukti Jaya obtained a response rate of 97.14% from teachers and 91.16% from students. at SDN 011 Lenggadai Hulu, the response rate was 98.57% for teachers and 88.63% for students; while at SDN 014 Pematang Sikat, the response rate was 97.14% for teachers and 93.20% for students, all of which were classified as highly practical. The effectiveness test results based on N-Gain calculations showed an increase in learning outcomes of 83.25%, 74.46%, and 76.4% respectively, which were classified as effective. Thus, this PBL-based animated video media is declared valid, practical, and effective, making it suitable for use as an innovative alternative in teaching IPAS material on the system of needs in Grade IV elementary school.